Evaluation of the Runoff and River Routing Schemes in the Community Land Model of the Yellow River Basin. (21st December 2017) - Sheng, Mingyang; Lei, Huimin; Jiao, Yang; Yang, Dawen
Abstract: Runoff and river routing schemes play important roles in land surface models (LSMs) because they regulate the soil moisture, heat flux, and vegetation dynamics of land surface processes and account for the carbon and nutrient transport in river channels. However, these schemes are often simplistic and conceptual. Hence, in this study, we focused on (1) evaluating these schemes in the Community Land Model (CLM) and (2) altering the model representations using physically based schemes based on a study of the Yellow River basin. For runoff simulation, CLM exhibits limitations in water‐limited areas, especially areas with aridity index values greater than 2. Additionally, CLM greatly overestimates runoff, and produces negative Nash‐Sutcliffe efficiency (NSE) coefficients, few quick flow variations, high quick flow index values, and large root mean square errors of total water storage. These issues were greatly improved by implementing schemes of physically based overland flow, lateral soil water flow, and interchange between groundwater and river water. Furthermore, for the river routing scheme, the use of 1‐D kinematic wave routing improved previously unrealistic aspects of the flood hydrographs (e.g., incorrect flood peak values and times) of the original CLM. Moreover, compared with using the grid element‐based river routing approach in CLM, the computational costs were reduced by up to 45% by implementing the flow interval element method. Finally, our results indicate that parameter calibration in CLM minimally improved the simulation performance in water‐limited areas, while physically based schemes generated better results. Key Points: The representation of saturated excess surface runoff was improved in semiarid and arid areas A 1‐D kinematic wave routing scheme was integrated into CLM Calibration of CLM cannot considerably improve the streamflow simulations in water‐limited areas